Sexual behaviors and status disclosure of adult HIV positive patients enrolled in care in Yola, Nigeria - Martins, Olutayo Folashade; Gyanchand Rampal, Lekhraj Rampal; Lye, Munn Sann; Mohd Sidik, Sherina; Othman, Norlijah; Iliyasu, Zubairu; Salawu, Fatai Kunle (The International Journal of Health Sciences and Research, 2016)
With the availability of ART in most parts of Nigeria, more HIV positive individuals are living healthy lives. In periods of illness, sexual activity may be the last thing on the mind of a HIV positive individual but when in good health, sexual activity is definitely expected. This study describes the baseline sexual behaviors and status behavior of a three arm single blind randomized controlled clinical trial involving 386 randomly selected and allocated adult HIV patients who were enrolled into ART at all four comprehensive ART sites in Yola. The intervention was 10 to 15 minutes clinic based Clinician Client Centered counseling. An interviewer administered validated structured questionnaire was used for data collection. One hundred and eleven (62.4%) of respondents were inconsistent condom users, 29 (7.5%) had more than one sexual partner/spouse while 33 (11.3%) were yet to disclose their status to their spouse(s) and/or sex partners. Inconsistent condom use, non-status disclosure and sex with an unsteady partner were the most common high risk behaviors. Behavioral interventions are thus needed to reduce HIV spread in these groups of people.